STRATEGI BADAN PENANGGULANGAN BENCANA DAERAH DALAM PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN DI KABUPATEN KEPULAUAN MERANTI TAHUN 2017 - Putri, Rossa Yuliana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The Forest and land fires are disasters that occur every year on peat area caused by two factors: natural and human factors. The forest and land fires produce a lot of dangerous smoke that can disrupt public health. In this case, the regional governmentshould have taken responsibility to overcome and reduce the risk of widespread forest and land fires inMeranti Islands District. Hence, Regional Disaster Management Agency (BPBD) was established three years ago as an extension of the National Disaster Management Agency (BNPB). This reaearch aimed to determine the strategy of the Regional Disaster Management Agency in the prevention of the forest and land fires in Meranti Island District in 2017. This study used a qualitative approach. The data were collected by using stakeholder elements in Kepulauan Meranti District in 2017. Purposive data was collected through informants. The technique of collecting data used interviewsand documentation studies. Lastly, the data were analysed by using the process of reducing, presenting, and verifying data. There were two results of this research that showed the strategy implemented by the Kepulauan Meranti BPBD in 2017. The first is a preventive strategy to prevent forest and land fires early for the future. The second is innovative strategies to prevent forest and land fires in the form of new innovations for renewal and cultivation forests with long-term goals.Â Keywords: Strategy, BPBD, Prevention, The Forest and Land firesÂ